2000
DOI: 10.1200/jco.2000.18.22.3809
|View full text |Cite
|
Sign up to set email alerts
|

The United Kingdom Children’s Cancer Study Group’s Second Germ Cell Tumor Study: Carboplatin, Etoposide, and Bleomycin Are Effective Treatment for Children With Malignant Extracranial Germ Cell Tumors, With Acceptable Toxicity

Abstract: Conservative surgery, a watch-and-wait approach after complete excision, and JEB for those requiring chemotherapy produced high cure rates and few serious complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
170
1
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(189 citation statements)
references
References 29 publications
14
170
1
4
Order By: Relevance
“…This view would be concordant with known clinical outcome data, which indicates that childhood MGCTs can be treated differently to their adult counterparts without adverse outcomes well into adolescence (Mann et al, 2000). Where the biological cut-off between childhood and adult MGCTs occurs, and what biology underpins this, has still to be elucidated.…”
Section: Discussionsupporting
confidence: 59%
“…This view would be concordant with known clinical outcome data, which indicates that childhood MGCTs can be treated differently to their adult counterparts without adverse outcomes well into adolescence (Mann et al, 2000). Where the biological cut-off between childhood and adult MGCTs occurs, and what biology underpins this, has still to be elucidated.…”
Section: Discussionsupporting
confidence: 59%
“…For 137 children treated with JEB in this trial, the 5-year EFS was 88% and OS was 91%, which was comparable to the outcomes using PEb, but with no reports of sensorineural hearing loss. 48 These results suggested that carboplatin could be a potential alternative to cisplatin in children when used in sufficient doses. This hypothesis forms the basis of an upcoming collaborative trial.…”
Section: Staging and Risk Groupsmentioning
confidence: 82%
“…For example, studies have reported similar outcomes in pediatric germ cell tumour patients treated using carboplatin, etoposide and bleomycin compared to treatment with cisplatin, etoposide and bleomycin but with less ototoxicity 53,54 and treatment with carboplatin, etoposide and bleomycin has been suggested as an alternative treatment in young children 55 . A possible role for carboplatin has also been suggested in the treatment of neuroblastoma, where one study reported similar survival between patients receiving cisplatin therapy and patients receiving partial substitution of cisplatin therapy with carboplatin 56 .…”
Section: How Should Patients Undergoing Cisplatin Therapy Be Managed mentioning
confidence: 83%